ASCITIC FLUID CULTIVATED ORGANISMS AND THEIR ANTIMICROBIAL RESILIENCE PATTERN IN PATIENTS WITH LIVER CIRRHOSIS - Khurram Baqai; Nasir Laique; Faisal Ziauddin (ziauddin University, 2019)
Background: Spontaneous bacterial peritoinitis is one of the life threatening complications of Cirrhosis of liver. Mortality and morbidity are high because of sepsis, hepatorenal syndrome and liver failure. Internati-l societies recommend the use of 3rd generation Cephalosporin as first line and quinolones and Amox-clav as second line of therapy. Development of resistance among microbials against these antibiotics has been reported during last several years. The purpose of this research is to determine the frequency of micro-organism cultivated in ascitic fluid and pattern of their resistance to antimicrobials at a tertiary care hospital. Methods: Ascitic fluid samples were received from both in-patients and out-patients in sterile leak proof containers. All micro-organisms isolated from ascitic fluid samples were included in the study. Ascitic fluid samples were inoculated on sheep blood agar, chocolate agar, MacConkey agar, according to standard microbiological protocol. Antimicrobial susceptibility testing was performed on MHA medium (Oxoid Ltd, England) using modified Kirby Bauer's disk diffusion method according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Results: Out of 356 ascitic fluid samples, 54(15.1%) of samples were culture positive. Esherichia coli (38.9%) was the most prevalent pathogen isolated, followed by Staphylococcus aureus(11.1%) and Acinetobacter species(7.4%). Frequency of strains resistant with Cefotaxime (100%), Ciprofloxacin (68.4%) and Amox-clav (57.1%) were remarkably high. Esherichia coli was mostly responsive with Amikacin, Meropenum, Cefoperazone/Sulbatum and Piperacillin/Tazobactum. Conclusion: Gram -ve bacteria has been remained main prevalent infectious organisms causing Spontaneous Bacterial Peritonitis. A high resistance pattern with Cephalosporins and Quinolones is frightening as these drugs have been considered as first line therapy in the management of Spontaneous Bacterial Peritonitis. Resistance profile is better with Amikacin, Meropenem, Cefoperazone/sulbactum and Piperacillin/Tazobactum.